Peranan Lembaga Perlindungan Saksi dan Korban (LPSK) Terkait Seorang Justice Collaborator dalam Sistem Peradilan di Indonesia: Studi Kasus Richard Eliazer - Alfin Noverlin; Syaiful Munandar (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study discusses the role of the Witness and Victim Protection Agency (LPSK) in providing protection for justice collaborators in the justice system in Indonesia. Justice Collaborators have an important role in uncovering organized crime. Lack of attention to justice collaborators and the absence of definite guarantees in the resolution of the criminal justice system make witnesses reluctant to cooperate. Therefore, Law 30 of 2014 LPSK in implementing and implementing protection for witnesses who cooperate must provide a sense of security from threats from perpetrators of crimes that are revealed. As a consequence and sacrifice of justice collaborators that must be appreciated by law. By using normative legal research methods and normative juridical approaches, this study examines the role of LPSK based on applicable laws and regulations and the impact of protection provided by LPSK to a Justice collaborator. The case study of Richard Eliezer shows how the role of LPSK in providing protection for justice collaborators is in accordance with applicable laws and regulations. The results of this study indicate that the protection provided by LPSK allows justice collaborators to provide information more safely and objectively